PENERAPAN DECISION MAKING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN AKUNTANSI - Khristina Sri Prihatin (FKIP, Universitas Banten Jaya, 2018)
This study was aimed to determine: 1) application of decision making learning model in class XI MA at Daar El- Istiqomah Sukawana, Serang city of Banten, academic year 2016/2017. 2) The improvement of the results of accounting learning by applying decision making learning model on the subject matter of Recording Transactions/ Documents into General Jurnal in class XI MA at Daar El-Istiqomah, Sukawana, Serang - Banten City in academic year 2016/2017.This research was a classroom action research (CAR). The research used two cycles and each cycle consisted of four steps. The subjects in this study was class XI in MA Daar El-Istiqomah Sukawana, Serang - Banten, that consist of 25 students. The object of this research was an implementation of decision making learning model.The results showed that the implementation of decision making learning model could be increased teacher and students activity. It could be seen that there were an increasing activity from cycle 1 to cycle 2. On cycle I, based on teacher observation, the activity reached 58% and in cycle II reached 88% . Students learning outcomes based on average pre test reached 45. While the post test on cycle 1 by applying the Decision Making learning model has increased 71.4, and the average in post test on cycle II increased quite significant than in cycle 1 that is 80,8.